แปลกแยก - วงศกร แกล้วกล้า (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The series "Alienation" was made from the idea that I want to change myself from introverted personality and rarely socialized with other people. I want to cure my personality that cause trouble through the work of this series. 'cosplaying' or role-playing as a character in a comic that I love makes me feel like I'm abandon my old self and become an comic character for a moment. As a childhood to played the role of various characters. This allows me to change myself a little bit and increase the courage to face up to the various situation. So I began to feel more confident. Since my first project has discussed my past about my introvert personality. And then my current thesis is about trying to transform myself into society by dressing as a comic imitation media as a lead.